Dossier II: Propuesta módulo de tratamiento para agresores sexuales juveniles en grupo - Pérez Fernández, Belén (Quadernos de criminología, 2022)
Over the years, Spain has been experiencing an increase in multiple perpetrator sexual assaults. Despite this, studies and research on this phenomenon are still scarce. However, it is known that a third of sexual assaults are committed by several perpetrators and that the average of these aggressors is between 19.3 and 26.9 years old. The sexual offender who commits an aggression with in group isn't the same as the one who acts alone, and, currently, there is no treatment module aimed at the circumstances surrounding the group factor, but exclusively at the individual. The gamification, dynamics of interaction and the composition of the group are the keys that will mark the lines of action and intervention in the creation of an effective treatment.